PELATIHAN PENGEMBANGAN RENCANA BISNIS UNTUK MENDUKUNG KEGIATAN BISNIS PADA FORUM USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) WONOKERTO, TURI, SLEMAN - Samlawi, Ahmad; Arianisari, Septiningdyah; Norviana, Syahida (LP2M STP Mataram, 2024)
The aim of the training is to develop a Business Plan as an active entrepreneurship methodology to enhance the analytical perception of Micro, Small, and Medium Enterprises (MSMEs) in Wonokerto, Turi, Sleman, Special Region of Yogyakarta. This training is expected to serve as an evaluation that contributes to the improvement of MSME Business Plans. The training participants consisted of 35 members from the Wonokerto MSMEs Forum. The training was conducted using three methods: lectures, tutorials, and discussions. The implementation of this community service can generally be categorized as successful, based on the evaluation results and the active participation of participants during the discussion and Q&A sessions